Euthanasia: another face of murder (2004)
Debate over euthanasia is not a recent phenomenon. Over the years, public opinion, decisions of courts, and legal and medical approaches to the issue of euthanasia has been conflicting. The connection between murder and euthanasia has been attempted in a few debates. Although it is widely accepted that murder is a crime, a clearly defined stand has not been taken on euthanasia. This article considers euthanasia from the medical, legal, and global perspectives and discusses the crime of murder in relation to euthanasia, taking into consideration the issue of consent in the law of crime. This article concludes that in the midst of this debate on euthanasia and murder, the important thing is that different countries need to find their own solution to the issue of euthanasia rather than trying to import solutions from other countries.